Estudos teóricos dos efeitos de binaridade na evolução estelar - Leandro Rocha Rimulo (2011)
The ATON code is a very known tool for modeling the stellar structure and evolution, which, in its standard form, simulates standard stars: stars not inuenced by any eects that could remove the spherical symmetry of its constitutive equations. In 1999, it was given to the code the possibility of simulating a rotating star, by using a technique which maintains the 1-dimensional character of the code. In 2006, tidal eects due to the potential generated by a companion star, considered a point star, were also included, using the same technique, making it possible for the code to simulate a binary system in the particular case that the systems orbit is circular and the orbital and rotation axis are parallel. In this present work, we theoretically investigated the gravitational and orbital eects originated by the presence of a companion star at the vicinity of the star which is modeled by the ATON code. We deduced a more general eective potential for the binary system, Ø, that allows for the system the possibility of having a non-circular orbit and the rotational axis of its components non-parallel to the orbital axis of the system, and we indicated how this new potential could be included in the code. This work conrms the previous ones, and it also signs their approximations possible weaknesses: dierential rotation, negligible second order terms of deformation and a point mass companion star. The new deduced potential is challenging in the sense that it presents time variations in a timescale much shorter than the usual evolutive time steps of the ATON code. In spite of that, for the particular case of an eccentric orbit and parallel axis, the inclusion of the new potential in the code may be simple. In this work we also discussed about the apsidal motion of binary systems, the main observational test for the developed theory. We made use of evolutionary tracks generated by the ATON code in the process. We veried the already known result that the presence of a close star generates more centrally condensed models, an eect that could alter sensitively the apsidal motion. Finally, in parallel with this work, we worked on the update of the saving mechanism of the ATON code: the checkpoint.